(untitled) (Journal of the College of Basic Education, 2022)
Since the dramatic formula of the Greek play was formed, which was codified by (Aristotle) ​​in his book (The Art of Poetry), and which most international writers, especially Europeans, followed in the production of the play, until that formula became a criterion against which theatrical productions are measured. Far from drama and theater, therefore, we find that most of the innovations and innovations in international drama dealt with textual content without the genre form.